A fuzzy sliding mode controller for power quality improvement of solar PV interleaved parallel inverters in a micro-grid. Issue 1 (31st December 2022) - Srinivasan, Sivaranjani; Arivukkannu, Ezhilarasi; Muthiah, Ramaswamy
Abstract : The paper attempts to develop a fuzzy based sliding mode controller (FSMC) for improving the quality of power in an interleaved inverter system. The framework involves boost inverters in parallel, operated from a solar PV source for offering the requirements of an ac load. It orients to evolve a rule based principle for engaging the gain of the FSMC in an effort to improve the quality of power delivered to the load through the inverter. The strategy augurs to derive the reference from the action of the controller and there generates the pulse width modulation (PWM) pulses for the switches in the inverter. The etiquettes incite to ensure equal sharing of current among the inverters in parallel and assuage to regulate the load voltage over the operating range. The MATLAB based simulation fosters brings out the merits of the controller over the fuzzy proportional integral (FPI) controller in terms of a lower THD and higher HSF for the output voltage. The prototype further serves to validate the simulated performance and illustrate its ability to suit real world systems.